Effect of Electromagnetic Force Caused by PMSM on the Vibration/Noise of Reciprocating Compressors - Chi-Sung Park; Jae-Hyun Kim; Soo-Hwan Park; Myung-Seop Lim (IEEE Access, 2023)
The use of pulse width modulation (PWM) to drive permanent magnet synchronous motors (PMSM) inevitably creates current harmonics. The generated current harmonics create harmonic components of the electromagnetic force, causing noise and vibration in the PMSM and affecting the applied system. In this paper, the effect of PMSM’s electromagnetic force on noise and vibration of a reciprocating compressor is analyzed. First, two PMSMs with different electromagnetic forces were designed. As the driving method, space vector PWM (SVPWM) was used, and the experimental current waveform was analyzed. Based on the Maxwell stress tensor method, the electromagnetic force of the PMSM was calculated and the noise/vibration characteristics were analyzed. Compressors were manufactured with two PMSMs with different electromagnetic forces and the noise/vibration test results were compared. The electromagnetic force of PMSM affected the noise of the compressor, especially in the domain of twice the carrier frequency, but did not affect the low-order vibrational displacement of the compressor. The finite element analysis method was used, and it was experimentally verified with the manufactured motor and compressor.